2013
DOI: 10.1093/nar/gkt962
|View full text |Cite
|
Sign up to set email alerts
|

GEISHA: an evolving gene expression resource for the chicken embryo

Abstract: GEISHA (Gallus Expression In Situ Hybridization Analysis; http://geisha.arizona.edu) is an in situ hybridization gene expression and genomic resource for the chicken embryo. This update describes modifications that enhance its utility to users. During the past 5 years, GEISHA has undertaken a significant restructuring to more closely conform to the data organization and formatting of Model Organism Databases in other species. This has involved migrating from an entry-centric format to one that is gene-centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 12 publications
4
94
0
Order By: Relevance
“…We continue to maintain links to mouse expression data from the Allen Institute (13), GENSAT (14), GEO (15) and EBI's Expression Atlas (16). We have added links to expression data from other vertebrate model organisms highly relevant for developmental research: zebrafish (ZFIN, 17), Xenopus (Xenbase, 18) and chicken (GEISHA, 19). …”
Section: Enhancements Of Data Structure and Web Interfacementioning
confidence: 99%
“…We continue to maintain links to mouse expression data from the Allen Institute (13), GENSAT (14), GEO (15) and EBI's Expression Atlas (16). We have added links to expression data from other vertebrate model organisms highly relevant for developmental research: zebrafish (ZFIN, 17), Xenopus (Xenbase, 18) and chicken (GEISHA, 19). …”
Section: Enhancements Of Data Structure and Web Interfacementioning
confidence: 99%
“…The most likely ligands involved in this step are FGF2, FGF8 and/or FGF9, all of which are expressed in the mesonephric region, and are known to have high affinity for FGFR2 (Antin et al, 2014;Martin et al, 2006;Yoshioka et al, 2005). Our study has also revealed that FGF signaling in the MFR is intracellularly transduced through the Ras/ERK pathway but not the PI3K/AKT pathway ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…For example, databases such as those hosted by the University of Arizona (Geisha) (Antin et al, 2013; Bell et al, 2004), provide powerful resources for the pattern of gene expression during embryogenesis. Furthermore, the advent of next generation sequencing technologies such as dSAGE and RNAseq provide whole transcriptome quantification and profiling not previously available for studies in avians.…”
Section: Methods: Techniques For Handling the Embryomentioning
confidence: 99%